Analisis Strategi Komunikasi Pemasaran Pegawai Barista Bitween.Sub dalam Menjaga Kualitas Pelayanan Pelanggan - Fitriah, Zulfa Amalia; Mirrotin, Bilqis Hurin; Putra, Andro Trifandi Armanda (Jurnal Ilmu Komunikasi, 2024)
A coffee shop is an entity that combines art and service, as is the case with the bitween.sub coffee shop which not only serves coffee drinks but creates quality service, so there needs to be a special role for a barista in an effort to maintain the quality of service to everyday customers. day through marketing communications concept. This research uses qualitative research methods by Bogdan and Tylor through observation and interviews, and data is obtained and analyzed by presenting sources including a barista and customers of the bitween.sub coffee shop. In the findings of this research, the baristas show that they use profiling techniques to serve customers. Apart from that, the baristas also build chemistry with customers as stated in the Company Operational Standards which are trained and implemented by the bitween.sub coffee shop in serving customers on a daily basis.